Pengaruh Perencanaan Penganggaran dan E-Procurement terhadap Penyerapan Anggaran - Ade Frankoe; Kamaludin Kamaludin; Fadli Fadli (UNIB Press, 2021)
The purpose of this study was to determine the effect of planning and procurement of goods and services on the absorption of the Regional Budget. The data used in this study are primary data obtained from the results of distributing questionnaires in Bangka Belitung and Lampung provinces. Number of samples is 192 respondents from 66 the Local Government Organizations of Bangka Belitung and Lampung Provinces. The data analysis method used is descriptive analysis and regression analysis. The results obtained are: (1) Budget planning has a positive and significant effect on budget absorption in Lampung Province and Bangka Belitung Province. This result means that the more planned the activity budget in each SKPD / OPD, the higher the absorption of the budget; and (2) E-Procurement has a positive and significant effect on budget absorption in Lampung Province and Bangka Belitung Province. This result means that the better the implementation of e-procurement (procurement of goods and services) in each SKPD / OPD, the higher the budget absorption.